Investigation of Antibacterial Effects of Different Plant Extracts and Essential Oils on Bacteria Isolated from Lakerda Products - Dilek KAHRAMAN YILMAZ; Nermin BERİK (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2023)
In this study, the in vitro antimicrobial effects of citrus flower, clove and orange peel essential oils and ethanolic extracts on different bacteria isolated from lakerda samples were investigated. It was determined that essential oils were more effective than ethanolic extracts. Citrus flower and clove essential oils showed strong effects on Pseudomonas fluorescens, Staphylococcus pasteuri, Staphylococcus equorum, Carnobacterium mobile, Carnobacterium maltaromaticum, Vibrio hibernica and Vibrio rumoiensis. Essential oils showed the highest inhibitory effect on C. mobile. It was found that the essential oil of citrus flower and clove were effective on C. mobile at concentrations 0.00977% and 0.00488%, respectively. It was determined that citrus essential oil provided a stronger inhibition on Staphylococcus pasteuri at a concentration of 0.3125%. The clove essential oil at a concentration of 1.25% had the least effect on S. pasteuri. In this study, it was determined that the essential oils of citrus flowers and clove had strong inhibitory effects on the tested bacteria. In conclusion, our findings supports that addition of citrus flowers and clove essential oils to lakerda had positive effects with respect to food safety.